Mucogingival surgery for root coverage using subepithelial connective tissue graft with tunnel and pouch technique - A case report (Indian Journal of Case Reports, 2018)
Marginal tissue recession, also known as gingival recession (GR), is a common condition seen in clinical practice. Along with unesthetic appearance, it also increases the chances of tooth hypersensitivity, root surface caries, abrasion, and pulpal hyperemia. When indicated, the correct mucogingival surgical procedure provides excellent stable results for such deformities. Various modalities such as a coronally repositioned flap, lateral pedicle flap, double papilla flap, and semilunar flap in combination with subepithelial connective tissue graft (SCTG) can be employed to treat GR. This article puts emphasis on a case report in which GR, due to toothbrush trauma, was covered using a tunnel and pouch technique combined with an SCTG harvested from the palate. The dual blood supply for the graft’s nutrition, originating from the connective tissue of both, the flap and periosteum along with the minimally invasive nature of the technique resulted in a clinical success. The case was followed up for 2 years subsequent to the procedure, where optimum root coverage for the operated teeth was noted.